Ella: sus muchas caras. Traducir poesía autóctona desde teorías feministas y poscoloniales - Chávez, Lidoly (El Colegio de México A.C., 2015)
The translation of Louis Halfe’s work into Spanish is only the first step in reflecting on the limited circulation of female indigenous literatures in the Americas. Through the linguistic transfer of her text Blue Marrow, we see a cultural revision of “peripheral” creators—the indigenous subject, the woman, the translator—who are now relegated to a secondary rank by the hegemonic literary canon.  A translation based on postcolonial and feminist theories, however, allows new audiences to witness  Halfe’s subversive spirit, as such a text provides Hispanic American cultures with new experiences  and strategies that disturb the dominant language. Halfe’s literature also contributes to a deepening awareness about the role of women in the colonial context and the transmission of memory.